Antagonists of the P2X7 receptor: Mechanism of enantioselective recognition using highly sulfated and sulfobutylether cyclodextrins by capillary electrokinetic chromatography. Issue 19 (18th July 2014) - Baudelet, Davy; Ghinet, Alina; Furman, Christophe; Dezitter, Xavier; Gautret, Philippe; Rigo, Benoit; Millet, Régis; Vaccher, Claude; Lipka, Emmanuelle; Chankvetadze, Bezhan
<x xml:space="preserve">Abstract</x> This work concerns the successful enantiomeric separation of pyroglutamic acid derivatives, known to be P2X7 receptor antagonists, achieved by electrokinetic chromatography. After a broad screening, two negatively charged cyclodextrins, sulfobutylether‐β‐cyclodextrin (SBE‐β‐CD), and highly sulfated‐γ‐cyclodextrin (HS‐γ‐CD) were chosen as stereoselective agents to cooperate with the BGE for complexation. A fused silica capillary coated with polyethylene oxide, filled with a phosphate buffer (25 mM, pH 2.5) containing various concentrations of CD, was used. Assuming a 1:1 stoichiometry, calculations of the binding constants, employing the three different linearization plots, were performed from the corrected electrophoretic mobilities values of the enantiomers, at different concentrations of SBE‐β‐CD and HS‐γ‐CD in the BGE. The highest complexation was found with the SBE‐β‐CD. Among the three equations, results showed better linearity (R2 > 0.99) using the y‐reciprocal fit. This plotting method was then performed to determine the binding constants of each enantiomer at different temperature for compounds 1 and 2 with SBE‐β‐CD and HS‐γ‐CD in order to access to the thermodynamic parameters of the eight complexes. The linearity of the Van't Hoff plot, in the range of 288–303 K leading to negative enthalpy values, showed that the complexation phenomenon is enthalpically controlled and thermodynamically favored.